2011
DOI: 10.1016/j.enzmictec.2011.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amines and aminoalcohols on bovine intestine alkaline phosphatase activity

Abstract: Bovine intestine alkaline phosphatase (BIALP) is widely used as a signaling enzyme in sensitive assays such as enzyme immunoassay (EIA). In this study, we evaluated the effects of various aminoalcohols and amines on the activity of BIALP in the hydrolysis of p-nitrophenyl phosphate (pNPP) at pH 9.8, at 20 °C. The k(cat) values at 0.05 M diethanolamine, 0.1 M triethanolamine, and 0.2 M N-methylethanolamine were 190±10, 840±30, and 500±10 s(-1), respectively. The k(cat) values increased with increasing concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
(41 reference statements)
4
11
0
Order By: Relevance
“…1). Values are in agreement with the ones from the supplier (Sigma) and found in the literature 1720 . ΔH is the enthalpy of the chemical reaction measured in bulk; values are reported in the literature for catalase 30 , urease 1 , triose phosphate isomerase 22 and measured by isothermal titration calorimetry for alkaline phosphatase (see Extended Data Fig.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…1). Values are in agreement with the ones from the supplier (Sigma) and found in the literature 1720 . ΔH is the enthalpy of the chemical reaction measured in bulk; values are reported in the literature for catalase 30 , urease 1 , triose phosphate isomerase 22 and measured by isothermal titration calorimetry for alkaline phosphatase (see Extended Data Fig.…”
Section: Figuresupporting
confidence: 91%
“…1). All enzymes followed Michaelis–Menten kinetics with k cat and K M values in agreement with those previously reported in the literature 1720 (Table 1). …”
supporting
confidence: 90%
“…BIALP-catalyzed hydrolysis of pNPP was performed as described previously. 21,22) Briefly, the reaction was initiated by mixing 2,000 mL of 0.3-6.0 mM pNPP in 1.0 M diethanolamine-HCl, 1.0 mM MgCl 2 , and 20 mM ZnCl 2 at pH 9.8 with 1,000 mL of 120 pM BIALP thermally treated in the presence of sugars (90 mM sucrose, 90 mM trehalose, 90 mM maltose, 180 mM glucose, or 180 mM fructose) or 120 or 240 pM BIALP thermally treated in the absence of y To whom correspondence should be addressed. Tel: +81-75-753-6266; E-mail: inouye@kais.kyoto-u.ac.jp Abbreviations: ALP, alkaline phosphatase; BIALP, bovine intestine alkaline phosphatase; EIA, enzyme immunoassay; pNPP, p-nitrophenyl phosphate sugars.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] It is now widely used to stabilize not only enzymes but also various biomaterials. We have found that amines, 21) aminoalcohols, 21) and polyethylene glycol 22) activate BIALP, suggesting that they can be used as activators of BIALP in EIA. In this study, we examined the effects of three disaccharides (sucrose, trehalose, and maltose) and two monosaccharides (glucose and fructose) on BIALP activity and stability.…”
mentioning
confidence: 99%
“…We have found that amines and aminoalcohols activate BIALP. 13) Polyethylene glycol (PEG) is a hydrophilic, biocompatible polymer. The covalent attachment of PEG to proteins (pegylation) is effective for advanced clinical uses.…”
mentioning
confidence: 99%